The genus Processa in the vicinity of Carrie Bow Cay (Belize) with description of a new species (Crustacea: Decapoda: Processidae) - de Grave, Sammy; Felder, Darryl. L. (Zootaxa, 2012)
Three species of the genus Processa are reported from shallow waters of Belize. Processa manningi, sp. nov., a newmember of the burrow-dwelling group, was most commonly found in burrows of the callianassid Neocallichirusgrandimana on a lower intertidal unvegetated sand flat. Both sexes of the new species, sometimes as mated pairs, wereobtained along with the host during sampling of burrows with yabby pumps. Processa bermudensis (Rankin) and Processafimbriata Manning & Chace occurred frequently in sweep net samples taken nocturnally in seagrass beds, but were alsotaken occasionally from interstices of eroded conch shells and other shallow rubble collected in daylight. Coloration is documented, and its utility as a character discussed. The genus has not been previously reported from Belize.